Reliability and Validity of an Ultrasound-Based Protocol for Measurement of Quadriceps Muscle Thickness in Children - Högelin, Emil Rydell; Thulin, Kajsa; von Walden, Ferdinand; Fornander, Lotta; Michno, Piotr; Alkner, Björn (Frontiers in Physiology, 2022)
Introduction and aims: Accurate determination of skeletal muscle size is of great importance in multiple settings including resistance exercise, aging, disease, and disuse. Ultrasound (US) measurement of muscle thickness (MT) is a method of relatively high availability and low cost. The present study aims to evaluate a multisite ultrasonographic protocol for measurement of MT with respect to reproducibility and correlation to gold-standard measurements of muscle volume (MV) with magnetic resonance imaging (MRI) in children. Material and methods: 15 children completed the study (11 ± 1 year, 41 ± 8 kg, 137 ± 35 cm). Following 20 min supine rest, two investigators performed US MT measurements of all four heads of the m. quadriceps femoris, at pre-determined sites. Subsequently, MRI scanning was performed and MV was estimated by manual contouring of individual muscle heads. Results: Ultrasound measurement of MT had an intra-rater reliability of ICC = 0.985–0.998 (CI 95% = 0.972–0.998) and inter-rater reliability of ICC = 0.868–0.964 (CI 95% = 0.637–0.983). The US examinations took less than 15 min, per investigator. Muscle thickness of all individual quadriceps muscles correlated significantly with their corresponding MV as measured by MRI (overall r = 0.789, p < 0.001). Conclusion: The results of this study indicate that US measurement of MT using a multisite protocol is a competitive alternative to MRI scanning, especially with respect to availability and time consumption. Therefore, US MT could allow for wider clinical and scientific implementation.